Design And Development Of Process And Production Plant For Agarwood Oil - Muhammad Nasardin, Norul Rasyidi (2018)
Agarwood oil is very valuable oil and widely used in medicine, perfume, religious, cultural applications and cosmetic industries. In addition, the production of agarwood has a diverse range of prospects in Malaysia. However, knowledge on distillation process and standard for quality of the oil are far from sufficient. Nowadays, the quality of agarwood oil is difficult to maintain because of the uncontrolled the process system. Therefore, the purpose of this research is to design a fully automated system for hydro distillation process that can produce higher oil yield with better quality with high monitoring security. The hydro distillation process takes into account of several parameters which is emphasizes on two most significant process parameters: temperature and pressure. In this study, the Agarwood raw materials will be soaked with mineral water for a certain period of time before going through the hydro-distillation process. The raw materials boiling will be closely monitored and will be automatically agitated at periodically at certain speeds by using a fully automated PLC-based control system with the help of HMI/SCADA. The whole hydro-distillation process itself can also be monitored and operated remotely using HMI/SCADA. For the result, the process with fully automated system has increased 60% oil yield compared to manual system. In addition, the yield of oil also increased by 13% using the inoculated wood (Roselle biotech formula Inoculation) compared to natural wood. The analysis of FTIR and GCMS has shown that there are less organic alcohol presence and many organic nature compound was detect. In conclusion, the improvement of the process system had been shown that the system has increases the profit, high monitoring, less human error, increases inefficiency of process and reduce capital cost.